2014
DOI: 10.3389/fimmu.2014.00576
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a Risk and Severity Factor in Rheumatic Diseases (Autoimmune Chronic Inflammatory Diseases)

Abstract: The growing body of evidence recognizing the adipose tissue (AT) as an active endocrine organ secreting bioactive mediators involved in metabolic and inflammatory disorders, together with the global epidemic of overweight and obesity, rise obesity as a hot topic of current research. The chronic state of low-grade inflammation present in the obese condition and the multiple pleiotropic effects of adipokines on the immune system has been implicated in the pathogenesis of several inflammatory conditions including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 123 publications
6
90
0
1
Order By: Relevance
“…The observed increased MSSS is independent of BMI, sex and disease duration. This apparent paradoxical regulation of adiponectin in patients with MS may be explained by a different pathophysiology of adipose tissue in these patients . Our results are in line with a recent report of Çoban et al .…”
Section: Discussionsupporting
confidence: 92%
“…The observed increased MSSS is independent of BMI, sex and disease duration. This apparent paradoxical regulation of adiponectin in patients with MS may be explained by a different pathophysiology of adipose tissue in these patients . Our results are in line with a recent report of Çoban et al .…”
Section: Discussionsupporting
confidence: 92%
“…Most research on prenatal and earlylife DDT exposure has focused on outcomes such as obesity, neurodevelopment, and breast cancer (37)(38)(39). However, shared mechanisms may provide links to RA; for example, endocrine disruption, inflammation, and stress response (40)(41)(42). In a US population sample (1999)(2000)(2001), organochlorine levels were elevated in women with self-reported RA (43).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, stimulated articular adipose tissue would highly produce classical adipokines and a wide range of pro‐inflammatory and anti‐inflammatory cytokines . Studies have demonstrated that adipokines, which have the function to modulate various processes including inflammatory and metabolism, might be involved in the pathophysiology of obesity‐related diseases including RA . Increased adipokine levels were also found in the plasma and synovial fluid from RA patients, and the results implied that adipokines were involved in the pathogenesis of RA by exerting effective modulatory effects on target tissues and cells including cartilage, synovium, bone, and various immune cells …”
Section: Introductionmentioning
confidence: 97%